Change in prevalence of psychological and economic abuse, and controlling behaviours against women by an intimate partner in two cross-sectional studies in New Zealand, 2003 and 2019. Issue 3 (23rd March 2021) - Fanslow, Janet; Malihi, Zarintaj; Hashemi, Ladan; Gulliver, Pauline; McIntosh, Tracey
Abstract : Objectives: Changes in reported lifetime prevalence of psychological abuse, controlling behaviours and economic abuse between 2003 and 2019, and past 12-month prevalence of psychological abuse by an intimate partner were examined. Design: Cross-sectional analysis. Setting and participants: Data came from two surveys of family violence in New Zealand, conducted in 2003 and 2019. Respondents were ever partnered women aged 18–64 years old (2003 n=2673; 2019 n=935). Main outcome measures: Prevalence rates for psychological abuse, controlling behaviours and economic abuse were compared between the two study years using logistic regression. Sociodemographic and economic correlates of each abuse subtype were investigated. Interactions were examined between sociodemographic factors and the study year for reported prevalence rates. Results: There was a reduction in reported past 12-month experience of two or more acts of psychological intimate partner violence (IPV) from 8.4% (95% CI 7.3 to 9.6) in 2003 to 4.7% (95% CI 3.2 to 6.2) in 2019. The reported lifetime prevalence of two or more acts of controlling behaviours increased from 8.2% in 2003 (95% CI 7.0 to 9.5) to 13.4% in 2019 (95% CI 11.0 to 15.7). Lifetime prevalence of economic IPV also increased from 4.5% in 2003 (95% CI 3.5 to 5.5) to 8.9% in 2019 (95% CI 6.7 to 11.1). Those who were divorced/separated or cohabiting, and those living in the most deprived areas were more likely to report past year psychological IPV, lifetime controlling behaviours and economic abuse. A higher proportion of women who were married or cohabiting reported controlling behaviours in 2019 compared with 2003. Conclusion: While the reduction in reported past year psychological IPV is encouraging, the increase in the lifetime prevalence of controlling behaviours and economic abuse from 2003 to 2019 is worth critical evaluation. Results highlight potential gaps in current IPV prevention programmes, the need to identify and address underlying drivers of abusive behaviour and the importance of measuring multiple forms of IPV independently.